Application of Glycerol for Induced Powdery Mildew Resistance in Triticum aestivum L. - Li, Yinghui; Song, Na; Zhao, Chuanzhi; Li, Feng; Geng, Miaomiao; Wang, Yuhui; Liu, Wanhui; Xie, Chaojie; Sun, Qixin (Frontiers in Physiology, 2016)
Previous work has demonstrated that glycerol-3-phosphate (G3P) and oleic acid (18:1) are two important signal molecules associated with plant resistance to fungi. In this article, we provide evidence that a 3% glycerol spray application 1-2 days before powdery mildew infection and subsequent applications once every 4 days was sufficient to stimulate the plant defense responses without causing any significant damage to wheat leaves. We found that G3P and oleic acid levels were markedly induced by powdery mildew infection. In addition, TaGLI1 (encoding a glycerol kinase) and TaSSI2 (encoding a stearoylacyl carrier protein fatty acid desaturase), two genes associated with the glycerol and fatty acid (FA) pathways, respectively, were induced by powdery mildew infection, and their promoter regions contain some fungal response elements. Moreover, exogenous application of glycerol increased the G3P level and decreased the level of oleic acid (18:1). Glycerol application induced the expression of pathogenesis-related (PR) genes (TaPR-1, TaPR-2, TaPR-3, TaPR-4, and TaPR-5), induced the generation of reactive oxygen species (ROS) before powdery mildew infection, and induced salicylic acid (SA) accumulation in wheat leaves. Further, we sprayed glycerol in a wheat field and found that it significantly (p value<0.05) reduced the severity of powdery mildew disease and lessened disease-associated kernel weight loss, all without causing any noticeable degradation in wheat seed quality.